Food safety in urban informal market food environment: A social practice perspective on coping strategies of vendors in Dhaka, Bangladesh - Md. Latiful Haque; Peter Oosterveer; Raffaele Vignola (PLoS ONE, 2026)
Informal food vendors in the Global South face challenges in managing food safety, necessitating strategies that address consumer concerns and market sustainability. This paper examines how informal vendors in Dhaka, Bangladesh, cope with these challenges. Framing food vending as a social practice, the study emphasises that food safety is a shared responsibility. Based on research involving 26 vendors, we explore their coping strategies for sourcing, processing, storage, and selling food. Through qualitative analysis, we identify three distinct vendor types—cooked food, wet market, and dry market vendors—each of them employing specific approaches to food safety management. This classification enables a closer exploration of diverse food safety management strategies. Our findings highlight how vendors’ material resources, skills, and daily social interactions with consumers shape their strategies, including information sharing, resource management, trust-building, and innovation. Given the disparities in resource access and skills, we advocate for a multi-faceted approach to food safety that aligns with vendors’ local practices.